Genetic Diversity and Taxonomic Implications of Diutina mesorugosa: A review (Research, Society and Development, 2025)
Diutina mesorugosa is a yeast emerging in hospital environments and has been isolated from different clinical samples in different locations around the World, although atypical as an etiological agent of human infection. Previous phylogenetic analyses assigned the species as Candida mesorugosa, but this yeast has been reclassified as D. mesorugosa. It is known that different species belonging to the same genus such as D. rugosa, D. pseudorugosa, and D. catelunata have also been isolated from clinical samples, and the D. rugosa species has been identified as an emerging opportunistic pathogen. These species have also been reclassified recently. The objective was to perform a literature review on the taxonomic aspects of the yeast D. mesorugosa to deepen the knowledge of the taxonomic classification and systematics of this species within the genus Diutina.